Philosophical Foundation, Application, and Controversies of Judicial Pardon in Islamic Criminal Law, Indonesian Penal Code, and the Criminal Justice System of Kuwait - Mahrus Ali; Hamad F. Al-Fahad; Wasikh Maulana (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
This article explores the philosophical foundation and scope of application of al-‘afwu ‘anil ‘uqubah in Islamic criminal law, judicial pardon in the Indonesian Penal Code, and pardon and reconciliation under the criminal justice systems of Kuwait. Adopting philosophical, statutory, conceptual and comparative approaches, it employs the judicial-normative research method to analyse legal principles, legal concepts, and legislation relevant to the subject matter and to the topic. The findings indicate that the philosophical rationale of al-‘afwu ‘anil ‘uqubah in Islamic criminal law is grounded in restorative and theological aims, limiting its application to specific offences such as qishash, certain hudud, and ta’zir. In contrast, the Indonesian Penal Code uses rechterlijke pardon to soften the rigidity of legalistic punishment, granting judges discretionary authority to withhold penalties in trivial cases, taking into account the offender’s circumstances and contextual factors. Meanwhile, the Kuwaiti criminal justice system, though influenced by Sharia principles, employs pardon and reconciliation primarily to control crime, granting extensive powers to the Amir, victims, and investigative bodies to commute or withdraw penalties in exchange for cooperation.